The Dynamics of Self-Esteem in Facing the Duck Syndrome Phenomenon Among University Students - Az Zahra, Ummu Hafadzoh; -, Ikhrom; Nurfitri, Aldila Dyas (Psikologi Prima, 2025)
Issues regarding the phenomenon of duck syndrome are increasingly prevalent among university students, where individuals appear calm on the surface but experience significant mental distress. The purpose of this study was to explore the impact of duck syndrome on college students' self-esteem and identify factors that lead to increased levels of anxiety, low self-efficacy, and depression. The method used was qualitative research with primary data collection through online interviews with 10 active university students from two target regions, West Java and Central Java. The results showed that students who face high academic pressure, heavy social expectations, and negative influence from social media tend to experience duck syndrome, which causes low self-esteem, increased anxiety, and depressive symptoms.